1997
DOI: 10.1096/fasebj.11.10.9271366
|View full text |Cite
|
Sign up to set email alerts
|

A role for uncoupling protein‐2 as a regulator of mitochondrial hydrogen peroxide generation

Abstract: According to the state of mitochondrial respiration, the respiratory chain generates superoxide anions converted into hydrogen peroxide. Two uncoupling proteins (UCP) able to modulate the coupling between the respiratory chain and ATP synthesis are now identified and could be involved in mitochondrial H2O2 generation. UCP1 is specific to brown adipose tissue (BAT) whereas UCP2 is expressed in numerous tissues, particularly in monocytes/macrophages. Preincubation of BAT mitochondrial fractions with GDP, an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
480
1
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(516 citation statements)
references
References 28 publications
29
480
1
6
Order By: Relevance
“…A strong link between decreased levels of UCP2 and Gpx1 overexpression is supported by the response of the WT islets to GPX1 mimic, ebselen, and the resistance of OE islets to H 2 O 2 -suppressed GSIS. However, the UCP2 decrease may not be simply attributable to the diminished intracellular ROS because of a possible two-way feedback mechanism for the interaction of UCP2 and H 2 O 2 [49]. While expression and function of UCP2 are activated by ROS [21], mitochondrial H 2 O 2 generation can be decreased by UCP2 [49].…”
Section: Discussionmentioning
confidence: 99%
“…A strong link between decreased levels of UCP2 and Gpx1 overexpression is supported by the response of the WT islets to GPX1 mimic, ebselen, and the resistance of OE islets to H 2 O 2 -suppressed GSIS. However, the UCP2 decrease may not be simply attributable to the diminished intracellular ROS because of a possible two-way feedback mechanism for the interaction of UCP2 and H 2 O 2 [49]. While expression and function of UCP2 are activated by ROS [21], mitochondrial H 2 O 2 generation can be decreased by UCP2 [49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mechanisms that reduce membrane potential could lower superoxide production. A negative regulation of the mitochondrial ROS production by UCPs was first suggested in 1997 [9]; Skulachev in 1998 [10] also suggested that superoxide production may be reduced by factors that decrease mitochondrial membrane potential. Thus, as superoxide production can be Abbreviations: 3HADH, 3-hydroxyacyl CoA dehydrogenase; ANT, adenine nucleotide translocator; CPT-I, carnitine-palmitoyl-transferase-I; CPT-II, carnitine-palmitoyl-transferase-II; CS, citrate synthase; FA, fatty acid; HNE, 4-hydroxynonenal; LCAD, long-chain acyl CoA dehydrogenase; LDCL, lucigenin-derived chemiluminescence; MACP, mitochondrial anion carrier protein; NEFA, non-esterified fatty acid; ROS, reactive oxygen species; SS, subsarcolemmal; UCP, uncoupling protein decreased by mild uncoupling [10,11], mitochondrial anion carrier proteins (MACPs) including uncoupling protein (UCP) and adenine nucleotide translocator (ANT) may have an inhibitory action on the overproduction of mitochondrial superoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their similarity of sequence, UCP2 and UCP3 were first suggested to play a role in regulated thermogenesis [2]. Later studies demonstrated that this may not be the case [3] and now evidence is accumulating in favour of a role in reducing the production of reactive oxygen species (ROS) by the mitochondria [4,5].…”
Section: Introductionmentioning
confidence: 99%